Geotechnical zoning using descriptive statistical parameters for Costa Rica’s soils - Baltodano-Goulding, Rafael (2024)
A geotechnical zoning was created using descriptive statistics for the soils found in Costa Rica, taking into consideration the geotechnical map and the climatic conditions of Costa Rica. This information can be used to provide additional information when geotechnical analyses and designs are to be performed through a probabilistic approach and an appropriate quantity of data is lacking to adequately allow for the statistical processing of soil parameters. Consideration of the Geotechnical Zoning included in the Costa Rica Foundation Code was taken. Additionally, Climatological Atlas of the National Meteorological Institute was also considered. As part of the results attained, the average values and the standard deviation of different types of soils were obtained. The geotechnical information on the different materials was obtained from geological surveys and private geotechnical studies. This data is important because when considering them, it is possible to reduce the uncertainty associated with the characteristics of the soil.